Diagnosis of gastro‐oesophageal reflux disease is enhanced by adding oesophageal histology and excluding epigastric pain. Issue 10 (20th March 2017) - Vakil, N.; Vieth, M.; Wernersson, B.; Wissmar, J.; Dent, J.
Summary: Background: The diagnosis of gastro‐oesophageal reflux disease (GERD) in clinical practice is limited by the sensitivity and specificity of symptoms and diagnostic testing. Aim: To determine if adding histology as a criterion and excluding patients with epigastric pain enhances the diagnosis for GERD. Methods: Patients with frequent upper gastrointestinal symptoms who had not taken a proton pump inhibitor in the previous 2 months and who had evaluable distal oesophageal biopsies were included (Diamond study: NCT00291746). Epithelial hyperplasia was identified when total epithelial thickness was at least 430 μm. Investigation‐based GERD criteria were: presence of erosive oesophagitis, pathological oesophageal acid exposure and/or positive symptom–acid association probability. Symptoms were assessed using the Reflux Disease Questionnaire and a pre‐specified checklist. Results: Overall, 127 (55%) of the 231 included patients met investigation‐based GERD criteria and 195 (84%) met symptom‐based criteria. Epithelial hyperplasia was present in 89 individuals, of whom 61 (69%) met investigation‐based criteria and 83 (93%) met symptom‐based criteria. Adding epithelial hyperplasia as a criterion increased the number of patients diagnosed with GERD on investigation by 28 [12%; number needed to diagnose (NND): 8], to 155 (67%). The proportion of patients with a symptom‐based GERD diagnosis who met investigation‐based criteria including epithelial hyperplasia was significantly greater when concomitant epigastric pain was absent than when it was present ( P < 0.05; NND: 8). Conclusions: Histology increases diagnosis of GERD and should be performed when clinical suspicion is high and endoscopy is negative. Excluding patients with epigastric pain enhances sensitivity for the diagnosis of GERD. Abstract : Linked Content This article is linked to Roman and Mion and Savarino et al papers. To view these articles visithttps://doi.org/10.1111/apt.14076 andhttps://doi.org/10.1111/apt.14412 .